Black Tungsten Nitride as a Metallic Photocatalyst for Overall Water Splitting Operable at up to 765 nm. (30th May 2017) - Wang, Yu Lei; Nie, Ting; Li, Yu Hang; Wang, Xue Lu; Zheng, Li Rong; Chen, Ai Ping; Gong, Xue Qing; Yang, Hua Gui
Abstract: Semiconductor photocatalysts are hardly employed for overall water splitting beyond 700 nm, which is due to both thermodynamic aspects and activation barriers. Metallic materials as photocatalysts are known to overcome this limitation through interband transitions for creating electron–hole pairs; however, the application of metallic photocatalysts for overall water splitting has never been fulfilled. Black tungsten nitride is now employed as a metallic photocatalyst for overall water splitting at wavelengths of up to 765 nm. Experimental and theoretical results together confirm that metallic properties play a substantial role in exhibiting photocatalytic activity under red‐light irradiation for tungsten nitride. This work represents the first red‐light responsive photocatalyst for overall water splitting, and may open a promising venue in searching of metallic materials as efficient photocatalysts for solar energy utilization.